Millenial Consumers’ Intention to Repurchase in The E-Commerce Market Post Covid-19 in Pidie Regency - Fakhrurrazi; Mahrizal; Fitriyani; Herizal (Business Review and Case Studies, 2022)
The purpose of this study was to investigate how millennial consumers' exploratory goals affected the Pidie Regency's post Covid-19 e-commerce market. In Pidie Regency, Aceh Province, 200 respondents participated in this study and all respondents as sample. The sampling quota was utilized because the millennial generation in Pidie Regency those who were born between 1982 and 2000 or who are now between the ages of 19 and 37 is the subject of the study. This study distributed online questionnaires through Google Forms to respondents who fell into the millennial demographic. Structural Equation Modeling (SEM) with the AMOS 22 device was the data analysis technique used. The test's findings revealed that millennial consumer satisfaction is significantly impacted by the quality of e-services. In order to boost client purchase intents from the quality of services offered, satisfaction acts as a mediator. Keywords: e-commerce market, millennial consumers, Pidie, SEM, post covid-19